Synthesis of three branched iminosugars [(3R,4R,5S)-3-(hydroxymethyl)piperidine-3,4,5-triol, (3R,4R,5R)-3-(hydroxymethyl)piperidine-3,4,5-triol and (3S,4R,5R)-3-(hydroxymethyl)piperidine-3.4,5-triol] and a branched trihydroxynipecotic acid [(3R,4R,5R)-3,4,5-trihydroxypiperidine-3-carboxylic acid] from sugar lactones with a carbon substituent at C-2 - Simone, M; Soengas, R; Jenkinson, S; Evinson, E; Nash, R; Fleet, G (2012)
Homochiral piperidines containing a quaternary carbon branch at C-2 of the piperidine ring may be made from readily available carbohydrate lactones containing a branched 2-C-hydroxymethyl substituent. This gives an easy access to the branched iminosugars. In particular a trihydroxypipecolic acid analogue, (3R,4R,5R)-3,4,5-trihydroxypiperidine-3-carboxylic acid, has been synthesised efficiently from the starting material d-ribose and (3S,4R,5S)-3-(hydroxymethyl) piperidine-3,4,5-triol was found to be a specific inhibitor of α-d-glucosidase from Bacillus Stearothermophilus with an IC 50 value of 93 μM. © 2012 Elsevier Ltd. All rights reserved.